2020
DOI: 10.1016/j.antiviral.2020.104781
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antiviral effect of novel fluoxetine analogues as enterovirus 2C inhibitors

Abstract: Enteroviruses (EV) are a group of positive-strand RNA (+RNA) viruses that include many important human pathogens (e.g. poliovirus, coxsackievirus, echovirus, numbered enteroviruses and rhinoviruses). Fluoxetine was identified in drug repurposing screens as potent inhibitor of enterovirus B and enterovirus D replication. In this paper we are reporting the synthesis and the antiviral effect of a series of fluoxetine analogues. The results obtained offer a preliminary insight into the structure-activity relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
(18 reference statements)
1
23
0
Order By: Relevance
“…The data suggested a worsening of patient condition, possibly due to its SSRI activity [26]. Additionally, our previous work showed that the antiviral activity of fluoxetine is unlikely to be decoupled from its SSRI activity [24,27]. This clearly demonstrates that more potent and safer molecules are needed for treatment of EV infections.…”
Section: Plos Biologymentioning
confidence: 93%
See 3 more Smart Citations
“…The data suggested a worsening of patient condition, possibly due to its SSRI activity [26]. Additionally, our previous work showed that the antiviral activity of fluoxetine is unlikely to be decoupled from its SSRI activity [24,27]. This clearly demonstrates that more potent and safer molecules are needed for treatment of EV infections.…”
Section: Plos Biologymentioning
confidence: 93%
“…Subsequently, protein was expressed for 16 h at 18˚C, with shaking at 200 rpm. Further protein purification steps were performed essentially as described previously [27], with the exception that TEV protease was replaced with 3C protease (Sigma-Aldrich). The final size-exclusion chromatography step was performed at 4˚C with buffer containing 25 mM Tris (pH 8), 300 mM NaCl, and 1 mM MgCl2, using a superose 6 increase 10/ 300 column GL (GE Healthcare Life Science, Eindhoven, The Netherlands).…”
Section: Plos Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas the number of clinical trials cannot be extensively multiplied, libraries of “old” drugs can be screened in vitro in medium- to high-throughput assays to significantly reduce the number of candidate molecules. In addition, screening of approved drugs can also pave the way for medicinal chemistry programs 6 . Screenings of drugs to be repositioned against SARS-CoV, MERS-CoV or other viruses already showed their relevance for the selection of antivirals active at least in vitro 7 9 .…”
Section: Introductionmentioning
confidence: 99%